Comparative bioavailability study of triflusal oral solution vs. triflusal capsules in healthy subjectsA single, randomized, two-way cross-over, open-label phase I study - Izquierdo, Iñaki; Borja, Javier; Rovira, Sandra; Pelagio, Pilar; Torres, Ferran; Cebrecos, Jesus; García-Rafanell, Julián (Arzneimittelforschung, 2010)
Triflusal (CAS 322-79-2) is an antiplatelet agent that irreversibly acetylates cyclooxy-genase isoform 1 (COX-1) and therefore inhibits thromboxane biosynthesis. The main metabolite of triflusal, 2-hydroxy-4-trifluoromethyl benzoic acid (HTB), possesses also antiaggregant activity. Recently a new oral 600 mg (10 ml) solution form of triflusal has been developed. The purpose of this clinical trial was to study the relative bioavailability of the new oral solution of triflusal versus the capsules formulation, both administered as a single dose.This was a randomized, two-way, cross-over, open-label, single-site phase I clinical trial, in 24 healthy volunteers who received triflusal as 600 mg oral solution and as two 300 mg capsules in a single administration separated by a washout period of at least 17 days. Blood samples were collected and plasma concentrations of HTB were measured. Pharmacokinetic parameters used for bio-equivalence assessment included AUC0–t, AUC0–∞ and Cmax. The formulations were considered bioequivalent if the geometric mean ratios of AUC0–t, AUC0–∞ and Cmax were within the predetermined equivalence range (80% to 125%). Toler-ability was based on the recording of adverse events (AEs), physical examination, electrocardiogram (ECG) and laboratory tests. The parameters for bioequivalence, mean [SD] values were as follows: AUC0–t (μg · h/ml): 3574.08 [628.17] for triflusal oral solution and 3901.78 [698.43] for triflusal capsules; AUC0–∞ (μg · h/ml): 4089.21 [842.54] for triflusal oral solution and 4471.33 [905.93] for triflusal capsules; Cmax (μg/ml): 91.24 [12.88] for triflusal oral solution and 88.61 [13.46] for triflusal capsules; Cmax/AUC0–∞ (h−1): 0.03 (0.00) for triflusal oral solution and 0.02 (0.00) for triflusal capsules. The 90% confidence intervals for the ratio experimental/control by analysis of variance after log transformed AUC0–∞, AUC0–t, and Cmax were within 80% to 125%. Similar results were found for the data without log transformation. All adverse events were of mild or moderate intensity and all subjects recovered. Nine and 12 subjects reported at least one adverse event during treatment with triflusal oral solution and with triflusal capsules, respectively. The most frequently reported adverse events were headache and dizziness.It was concluded that the 600-mg solution of triflusal appeared to be bioequivalent to the reference formulation capsules. Both formulations were well tolerated.
Keywords: Antiplatelet agents; CAS 322-79-2; COX-1 inhibitors; Triflusal, bioavailability, capsule, oral solution